APPLICATION OF SELF-CONTROL TECHNIQUES TO REDUCE CONSUMPTIVE BEHAVIOUR IN STUDENTS RECEIVING KIP PGRI BANYUWANGI UNIVERSITY: PENERAPAN TEKNIK SELF-CONTROL UNTUK MENGURANGI PERILAKU KONSUMTIF PADA MAHASISWA PENERIMA KIP UNIVERSITAS PGRI BANYUWANGI - Adi Santoso; Heribertus Wicaksono; Ratna Wulandari (BIMBINGAN DAN KONSELING BANYUWANGI, 2023)
The study was conducted to determine the effectiveness of group guidance with Self-Control techniques to reduce consumptive behavior in KIP recipient students. This research uses quasi-experiment with one group pretest and posttes design. The research sample was selected using nonprobability sampling design technique using purposive sampling. The sample selection obtained 5 students from a total of 30 students who were categorized as high consumptive behavior questionnaire scores. The data collection technique used is a consumptive behavior questionnaire. Researchers used data analysis techniques with the Statistical Program For Social Sciences (SPSS) 2.5 for windows 11 test, obtained a t value of 34.785, which means that there has been a decrease in students' insecure feelings. With df = n-1 obtained df = 4 at a significant level of 5% then obtained ttabel 2.132, meaning t count> ttabel (34.785> 2.132). Thus it can be concluded that Ha which reads "Group guidance with Self-Control techniques has an effect in reducing consumptive behavior in students receiving KIP PGRI Banyuwangi University." accepted. The results showed that group guidance with Self-Control techniques proved effective in reducing consumptive behavior in students receiving KIP at PGRI Banyuwangi University.